PELATIHAN PEMANFAATAN LIMBAH SEDOTAN AQUA GELAS UNTUK PEMBELAJARAN MUATAN LOKAL BAGI GURU SMP DI KABUPATEN SLEMAN - budiastuti, dkk, emy (Universitas Negeri Yogyakarta, 2009)
AbstractThe Purpose of which wish to be reached through of PPM activity inthe form of applying activity of Sains and technology, be as follows : 1)Gives knowledge to teacher of Junior High School in choosing study of onPKK 2) Gives information to the teacher about limitation way to overcomeof supporting facilities for clan infrastructure in study of Skill Education onPKK, 3) Gives knowledge to the teacher about way of exploiting thebeverage industrial disposal around the school, 4) Trains skill of teachermakes multifarious of lenan household by exploiting waste industrybeverage, such as: Toper, tablecloth, etcThis Training activity was done in Cloth Lab of PTBB FT UNY on24 July 2008 until 14 August 2008. The Participant is 21 teacher’s of JuniorHigh Scholl in Yogyakarta. Method applied in this activity are discourse,discussion - information, demonstration and experiment.They made of lenan household single form of diametrical and circle,multiple form of diametrical and circle, and lenan with various technique of“meronce”. Each participant makes four kinds of object, out of five objectsplanned. Based on evaluation result, this activity was attractive and its canbe utilized and developed in school as component of skill teaching of PKK.And it can be to public. This Activity assessed to be very useful so thatparticipant expects for the next activity for developing skill teaching ofPKK for junior high school’s student. Training activity by participantassessed to be very useful so that they expect in order to keep activity ofcontinuation with different topic, though still exploits waste as componentof mainly.Keywords: aqua glass straw waste and skill teaching material